The false academy: predatory publishing in science and bioethics - Eriksson, Stefan (Med Health Care Philos, 2016)
This paper describes and discusses the phenomenon ‘predatory publishing’, in relation to both academic journals and books, and suggests a list of characteristics by which to identify predatory journals. It also raises the question whether traditional publishing houses have accompanied rogue publishers upon this path. It is noted that bioethics as a discipline does not stand unaffected by this trend. Towards the end of the paper it is discussed what can and should be done to eliminate or reduce the effects of this development. The paper concludes that predatory publishing is a growing phenomenon that has the potential to greatly affect both bioethics and science at large. Publishing papers and books for profit, without any genuine concern for content, but with the pretence of applying authentic academic procedures of critical scrutiny, brings about a worrying erosion of trust in scientific publishing.